ASSESSMENT OF RISK FACTORS AND DETERMINING THE LEVEL OF PREVENTABLE FETAL DEATH IN WOMEN WITH TROUBLED PREGNANCY - M.YA. KAMILOVA; P.A. DZHONMAKHMADOVA; F.R. ISHAN-KHODZHAEVA (Паёми Сино, 2020)
Objective: To examine the risk factors of stillbirth in the Republic of Tajikistan.